PENGARUH PAPARAN CAHAYA BIRU PADA PERANGKAT DIGITAL TERHADAP KESEHATAN MATA: TINJAUAN LITERATUR - Nafiisah, Nafiisah; Setyawan, Agus (Mandala Of Health, 2024)
Exposure to blue light from digital devices such as smartphones, tablets, and computers has become a major concern for eye health. Blue light, with wavelengths between 400-500 nanometers, can penetrate deeper into the eye and potentially cause retinal damage. This article reviews various studies assessing the impact of blue light on eye health, including the risks of developing computer vision syndrome, myopia, and age-related macular degeneration (AMD). Although the use of blue-blocking lenses has been suggested as a preventive measure, its long-term effectiveness requires further investigation. Other strategies, such as screen time regulation and the use of blue light-reducing software, are also analyzed as part of efforts to mitigate the negative effects of blue light. The findings from this review indicate that while there is potential risk from blue light exposure, more research is needed to develop more effective preventive strategies and to understand its long-term impact on eye health.